Work–Family Conflict in Sri Lanka: Negotiations of Exchange Relationships in Family and at Work - Kailasapathy, Pavithra; Metz, Isabel (The Journal of Social Issues, 2012)
This study's aim is to understand how individuals who are part of dual‐earner couples experience and deal with work–family conflict in Sri Lanka. Twenty‐five interviews were conducted to identify if and how couples negotiated within their marital relationships, and between themselves and their supervisors, to reduce or cope with work–family conflict. The interviews indicated that negotiations at home and at work concerned contributions to the exchange relationship and were unlikely to adversely affect the (home or work) exchange relationships. Negotiations at home were more likely to be initiated by women than men. Further, the interviews revealed an influence of spouse's gender role ideology on the success of the negotiation at home. Negotiations at work were more likely to be initiated by the interviewees than by their supervisors. The results suggest that individuals in cultures with high power distance should still initiate negotiations when they feel it is possible to obtain favorable outcomes.